Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Is our understanding of aquatic ecosystems sufficient to quantify ecologically driven climate feedbacks? - Corday R. Selden; Richard LaBrie; Laura C. Ganley; Daniel R. Crocker; Ohad Peleg; Danielle C. Perry; Hannah G. Reich; Matthew Sasaki; Patricia S. Thibodeau; Jana Isanta‐Navarro (Global Change Biology, 2024)
The Earth functions as an integrated system—its current habitability to complex life is an emergent property dependent on interactions among biological, chemical, and physical components. As global warming affects ecosystem structure and function, so too will the biosphere affect climate by altering atmospheric gas composition and planetary albedo. Constraining these ecosystem‐climate feedbacks is essential to accurately predict future change and develop mitigation strategies; however, the interplay among ecosystem processes complicates the assessment of their impact. Here, we explore the state‐of‐knowledge on how ecological and biological processes (e.g., competition, trophic interactions, metabolism, and adaptation) affect the directionality and magnitude of feedbacks between ecosystems and climate, using illustrative examples from the aquatic sphere. We argue that, despite ample evidence for the likely significance of many, our present understanding of the combinatorial effects of ecosystem dynamics precludes the robust quantification of most ecologically driven climate feedbacks. Constraining these effects must be prioritized within the ecological sciences for only by studying the biosphere as both subject and arbiter of global climate can we develop a sufficiently holistic view of the Earth system to accurately predict Earth's future and unravel its past.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Invasion of Siberian Elm (Ulmus pumila) Along the South Platte River: the Roles of Seed Source, Human Influence, and River Geomorphology - Lindsay V. Reynolds; Laura G. Perry; Patrick B. Shafroth; Gabrielle Katz; Andrew Norton (Wetlands, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Divergent effects of land-use, propagule pressure, and climate on woody riparian invasion - Laura G. Perry; Lindsay V. Reynolds; Patrick B. Shafroth (Biological Invasions, 2018)

Riparian Soil Development Linked to Forest Succession Above and Below Dams Along the Elwha River, Washington, USA - Laura G. Perry; Patrick B. Shafroth; Steven S. Perakis (Ecosystems, 2017)

Vulnerability of riparian ecosystems to elevated CO 2 and climate change in arid and semiarid western N orth A merica - Laura G. Perry; Douglas C. Andersen; Lindsay V. Reynolds; S. Mark Nelson; Patrick B. Shafroth (Global Change Biology, 2012)
Riparian ecosystems, already greatly altered by water management, land development, and biological invasion, are being further altered by increasing atmospheric CO 2 concentrations ([ CO 2 ]) and climate change, particularly in arid and semiarid (dryland) regions. In this literature review, we (1) summarize expected changes in [ CO 2 ], climate, hydrology, and water management in dryland western N orth A merica, (2) consider likely effects of those changes on riparian ecosystems, and (3) identify critical knowledge gaps. Temperatures in the region are rising and droughts are becoming more frequent and intense. Warmer temperatures in turn are altering river hydrology: advancing the timing of spring snow melt floods, altering flood magnitudes, and reducing summer and base flows. Direct effects of increased [ CO 2 ] and climate change on riparian ecosystems may be similar to effects in uplands, including increased heat and water stress, altered phenology and species geographic distributions, and disrupted trophic and symbiotic interactions. Indirect effects due to climate‐driven changes in streamflow, however, may exacerbate the direct effects of warming and increase the relative importance of moisture and fluvial disturbance as drivers of riparian ecosystem response to global change. Together, climate change and climate‐driven changes in streamflow are likely to reduce abundance of dominant, native, early‐successional tree species, favor herbaceous species and both drought‐tolerant and late‐successional woody species (including many introduced species), reduce habitat quality for many riparian animals, and slow litter decomposition and nutrient cycling. Climate‐driven changes in human water demand and associated water management may intensify these effects. On some regulated rivers, however, reservoir releases could be managed to protect riparian ecosystem. Immediate research priorities include determining riparian species' environmental requirements and monitoring riparian ecosystems to allow rapid detection and response to undesirable ecological change.

Immobilizing nitrogen to control plant invasion - Laura G. Perry; Dana M. Blumenthal; Thomas A. Monaco; Mark W. Paschke; Edward F. Redente (Oecologia, 2010)

Native cover crops suppress exotic annuals and favor native perennials in a greenhouse competition experiment - Laura G. Perry; Spencer A. Cronin; Mark W. Paschke (Plant Ecology, 2009)

Concentrations of the Allelochemical (±)-Catechin IN Centaurea maculosa Soils - Laura G. Perry; Giles C. Thelen; Wendy M. Ridenour; Ragan M. Callaway; Mark W. Paschke; Jorge M. Vivanco (Journal of Chemical Ecology, 2007)

No evidence for root-mediated allelopathy in Centaurea solstitialis, a species in a commonly allelopathic genus - Bo Qin; Jennifer A. Lau; Joseph Kopshever; Ragan M. Callaway; Heather McGray; Laura G. Perry; Tiffany L. Weir; Mark W. Paschke; Jose L. Hierro; John Yoder; Jorge M. Vivanco; Sharon Strauss (Biological Invasions, 2007)

Light competition for invasive species control: A model of cover crop–weed competition and implications for Phalaris arundinacea control in sedge meadow wetlands - Laura G. Perry; Susan M. Galatowitsch (Euphytica, 2006)

Zinc Toxicity Thresholds for Reclamation Forb Species - Mark W. Paschke; Laura G. Perry; Edward F. Redente (Water, Air, & Soil Pollution, 2006)

The influence of light availability on competition between Phalaris arundinacea and a native wetland sedge - Laura G. Perry; Susan M. Galatowitsch (Plant Ecology, 2004)